2018
DOI: 10.1093/infdis/jiy404
|View full text |Cite
|
Sign up to set email alerts
|

Host Gene Expression Kinetics During Treatment of Tuberculosis in HIV-Coinfected Individuals Is Independent of Highly Active Antiretroviral Therapy

Abstract: Blood transcriptomic profiles can potentially be used as biomarkers to discriminate the different clinical stages of tuberculosis in HIV-coinfected individuals and to monitor tuberculosis treatment responses in both HAART recipients and untreated individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…This is the first multi-site, prospective study analyzing unstimulated whole blood-derived RNA expression profiles of four endemic populations using dcRT-MLPA, a focused gene expression profiling platform for monitoring gene expression in large cohorts 29,34 . We showed that host RNA expression levels discriminate various stages of disease thereby offering potential for leprosy diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first multi-site, prospective study analyzing unstimulated whole blood-derived RNA expression profiles of four endemic populations using dcRT-MLPA, a focused gene expression profiling platform for monitoring gene expression in large cohorts 29,34 . We showed that host RNA expression levels discriminate various stages of disease thereby offering potential for leprosy diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as RNA-Seq and microarray are costly, technically challenging and require high RNA concentrations which limits their application for large cohorts. Therefore, a selection of genes related to immune-mediated inflammatory pathways, which play a role in the immunopathology of leprosy can be assessed by dcRT-MLPA 29,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of IFN-γ-producer cells in typical TB granuloma formation, we therefore hypothesize that individuals with a defective NLRC4/IL18 axis are not able to effectively contain mycobacteria within granulomas, leading to eventual extra-pulmonary dissemination. Accordingly, at least in HIV-infected patients, the expression of NLRC4 significantly increased in the blood of individuals with a more severe form of TB (41). Moreover, it is interesting to remember that lossof-function SNVs in NLRC4 have been found in HIV patents with severe TB (36) and in patients with cystic fibrosis affected by severe lung infections (42), reinforcing the important and poorly investigated role of NLRC4 in lung immunity and pulmonary diseases.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a recently described 7gene signature differentiated active TB from latent TB in subjects with concurrent HIV infection, regardless of HIV treatment status. 88 Importantly, these signatures are generalizable across diverse populations; one classifier that distinguished active TB from pneumonia had an AUC of 0.96 in an American cohort and 0.91 in a Sub-Saharan African cohort. 89 Given the widespread global disease burden of TB, the generalizability of these signatures is vital.…”
Section: Tuberculosismentioning
confidence: 99%